Interaction study of astilbin, isoastilbin and neoastilbin toward CYP2D6 by multi‐spectroscopy and molecular docking. (2nd June 2021) - Tao, Yanzhou; Fan, Yangyang; Liu, Guiming; Zhang, Yuhang; Wang, Meizi; Wang, Xiaolin; Li, Li
Abstract: Astilbin, isoastilbin and neoastilbin are the three flavonoid isomers prevalent in Rhizoma Smilax glabra . The interactions between human cytochrome P450 2D6 (CYP2D6) and the three isomers were investigated by multiple spectroscopic coupled with molecular docking. As a result, the fluorescence intensity of CYP2D6 was quenched statically by the three isomers. Meanwhile, astilbin had the strongest binding ability to CYP2D6, followed by isoastilbin and neoastilbin under the identical temperature. Synchronous fluorescence, three‐dimensional fluorescence, ultraviolet‐visible spectroscopy, circular dichroism and Fourier‐transform infrared spectra confirmed that the conformation and micro‐environment of CYP2D6 protein were changed after binding with the three isomers. As suggested from molecular docking, the three isomers had strong binding affinity to CYP2D6 via the bonding of hydrogen and van der Waals forces, and the results were in agreement with the fluorescence results. The findings here suggested that astilbin, isoastilbin and neoastilbin may cause the herb–drug interactions for their inhibition of CYP2D6 activity. Abstract : The interactions between astilbin, isoastilbin and neoastilbin with CYP2D6 have been investigated. Results revealed that astilbin had the strongest binding ability to CYP2D6, followed by isoastilbin and neoastilbin under the identical temperature. Van der Waals force or Hydrogen bonding force play major role in the binding process.